Preliminary evaluation of full volume strain measurement in patellar cartilage following osteochondral allograft transplantation using magnetic resonance imaging - Hernández Lamberty, Michael A.; Villacís Núñez, Carla Nathaly; Scheven, Ulrich; Grant, John A.; Arruda, Ellen M.; Coleman, Rhima M. (Frontiers in Bioengineering and Biotechnology, 2026)
IntroductionArticular cartilage (AC) defects of the patellofemoral joint (PFJ) are clinically challenging and mechanically demanding. Osteochondral allograft (OCA) transplantation is the standard treatment for large cartilage injuries; however, little is known about intra-tissue mechanics after transplantation. Computational models suggest that cartilage thickness mismatch concentrates stresses at donor–recipient interfaces in OCA-treated patella, but direct experimental evidence is scarce. Local cartilage strain is closely linked to tissue health; therefore, the goal of this work was to provide a preliminary, full volume assessment of patellar cartilage mechanics before and after OCA transplantation.MethodsA displacement-encoded MRI sequence was used to quantify full volume displacement and strain fields in human patellar AC before and after OCA transplantation under controlled indentation. Intact cadaveric patellae (n = 4) were prepared, with three serving as recipients and one as donor. Samples were cyclically compressed in a custom-built rig using nominal displacements of 1 and 2 mm. The complex phase data were unwrapped and converted to displacements; the Green–Lagrange strain tensor was computed using a finite element framework in FEniCS. Minimum principal strain (Emin) and maximum shear strain (Emaxshear) were analyzed. Donor–recipient step-off distance, representing cartilage-level geometric mismatch, was measured at the graft interface.ResultsGlobal displacement fields were similar between intact and OCA samples, with spherical indentation exhibiting through-thickness compression and lateral displacement in longitudinal and transverse directions. Emin localized beneath the indenter, while Emaxshear concentrated near the articular surface. OCA-transplanted samples exhibited localized changes in strain distribution near portions of the graft rim, though these features varied across samples. Top-view percentile maps highlighted redistributed high-strain regions in some OCA samples. Exploratory step-off plots showed sample-specific directional trends between geometric mismatch and donor-recipient strain differences, though these trends were not consistent across all samples.DiscussionThis exploratory study provides the first experimental full volume displacement and strain distributions of patellar cartilage after OCA transplantation. The localized strain variations observed after transplantation should be interpreted descriptively, given the single-donor design and sub-physiological loading. These results establish an experimental foundation for validating computational models of the donor-recipient cartilage interaction and geometric mismatch following OCA transplantation and work investigating OCA mechanics under physiological loading.